Flexible and free-standing SiOx/CNT composite films for high capacity and durable lithium ion batteries. (November 2019) - Guo, Wenlei; Yan, Xiao; Hou, Feng; Wen, Lei; Dai, Yejing; Yang, Deming; Jiang, Xiaotong; Liu, Jian; Liang, Ji; Dou, Shi Xue
Abstract: Flexible and free-standing electrode materials are prerequisite and key components for next-generation flexible energy storage and conversion devices. However, it is still a chanllenge to fabricate these materials from a continuous, straightforward, and facile method. Herein, we report a flexible composite film with silicon oxides decorated on few-walled carbon nanotubes, which can be continuously fabricated and directly drawn from the hot zone of the reactor. The composite film can be readily used for electrochemical lithium ion storage with high and reversible specific capacity, good rate capability, and excellent cycling performance. These exceptional characteristics make it very promising for flexible energy storage and other emerging applications. Graphical abstract: A continuous, flexible, and free-standing composite SiO x /CNTs film has been fabricated by the one-step and direct-injection floating catalyst chemical vapor deposition method and utilized for high performance electrochemical lithium ion storage. The materials' very unique and favorable structural and compositional characteristics have resulted in high capacity, excellent rate capability, and good cyclability for lithium ion storage applications. Image 1